Education-art-city: political and poetics interventions - Renata Sieiro Fernandes
This article is based on an action-research in development with two NGO's from the periphery of Campinas. This involves a training course for teachers and coordinators as a strategy for training in the field of non-formal education. This course aims to reflect and act on the city's spaces as sites of non-formal education, aesthetic appreciation and engage in micro-political actions, artistic, symbolic and poetic, through interventions in public space.